"I'm 100% for it! I'm a convert!": Women's experiences of a yoga programme during treatment for gynaecological cancer; an interpretative phenomenological analysis. Issue 1 (February 2015) - Archer, S.; Phillips, E.; Montague, J.; Bali, A.; Sowter, H.
Highlights Gynaecological cancer patients took part in a 10-week course of Hatha yoga. Patients took part in focus groups analysed with interpretative phenomenological analysis. The women's perceptions of the programme were generally positive; many found benefits. Previously unseen view of the patient experience of participating in a yoga intervention.